2020
DOI: 10.1097/hmr.0000000000000297
|View full text |Cite
|
Sign up to set email alerts
|

Examination of nursing home financial distress via Porter’s five competitive forces framework

Abstract: Background Nursing homes face increased risk of closure because of poor financial performance. Purpose Using resource dependency theory, Porter’s Five Forces of Competition framework, and Altman’s Z-score model, this study examines the relationship between market factors and nursing home financial distress. Methodology/Approach This study utilizes Medicare Cost Reports, LTCFocus, Certification and Survey Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The Weighting of the Subcriteria Related to Each of the Forces. The results of Zhao's research are in line with the results of the present study and confirm it Lord et al (2021). concluded that the impact of foreign market forces on the financial problems of nursing homes is limited, but organizational level variables have a significant effect on these problems.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The Weighting of the Subcriteria Related to Each of the Forces. The results of Zhao's research are in line with the results of the present study and confirm it Lord et al (2021). concluded that the impact of foreign market forces on the financial problems of nursing homes is limited, but organizational level variables have a significant effect on these problems.…”
supporting
confidence: 89%
“…The results of Zhao’s research are in line with the results of the present study and confirm it. Lord et al (2021) concluded that the impact of foreign market forces on the financial problems of nursing homes is limited, but organizational level variables have a significant effect on these problems. Similarly, the results of the present study show that due to the conditions of economic sanctions in the study population, foreign market forces are not colored, and unlike the results of research by Lord et al (2021), organizational level variables in this market are weak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The affiliation of for-profit NHs with chains has been addressed in the literature that analyses the performance of NHs, especially in relation to financial performance [ 11 , 14 , 15 , 16 ] and, to a lesser extent, in relation to quality [ 12 , 17 , 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, in recent decades, there has been an increase in the growth of chain affiliation in the NH industry [ 11 ]. The affiliation of for-profit NHs with chains has been addressed in the literature that analyses the performance of NHs, especially in relation to financial performance [ 11 , 14 , 15 , 16 ] and, to a lesser extent, in relation to quality [ 12 , 17 , 18 ]. Belonging to a chain allows the standardisation of certain care processes, which can contribute to improving [ 19 ] or worsening the quality [ 17 ].…”
Section: Introductionmentioning
confidence: 99%